Genetic and environmental factors affecting growth and sex ratio in the Nile tilapia :Oreochromis niloticus L. - Jose S Abucay (1997)
The experiments described in this thesis were performed to study and evaluate a number of relevant issues associated with the YY male technology. YY males are expected to produce all-male progeny. However, a small proportion of females have usually been observed in the progeny of XX x YY crosses. A series of experiments evaluating the effect of temperature and salinity on sex ratio in sexually undifferentiated putative all-female, all-male and YY males were conducted. High temperature (36°C) was observed to affect the sex ratio towards male and towards female in different circumstances. Purebred YY males (Egypt-Swansea strain) were found to be sensitive to high temperature. No effect of salinity on sex ratio was observed. Improving the growth of genetically male tilapia (GMT) through crossbreeding has been initiated. An initial study showed the hybrids had better growth than purebred progeny (Abucay, 1996). A follow up study evaluating the growth and sex ratio of progeny in a 2 x 2 diallele cross of Egypt-Swansea and Egypt-ICLARM strains using YY males as broodstock was performed. A parallel study was also conducted to determine the capacity of YY males in the Egypt-Swansea strain to sire all male progeny in crosses with females from a number of strains in O. niloticus. In the diallele cross, the reciprocal hybrids had a higher mean growth that the smaller parent and parental mean but not higher than the larger parent. In the parallel study, YY males were observed to be capable of siring high proportion of male progeny (93.12 to 100%) in the inter strain crosses. The growth of GMT, genetically female tilapia (GFT) and mixed-sex tilapia (MST) was evaluated; (i) during a period of androgen hormone treatment designed to alter the phenotypic sex, (ii) during the post-treatment period, and (iii) during the late life stages in monosex and mixed-sex culture environments. GMT was observed to exhibit faster growth at the early ages. No anabolic effect of the hormone was observed during the period of hormone treatment and posttreatment. The sex-reversed genetic females appeared to grow better than the genetic males during the late life stages. The culture of all females appears to have great potential. A series of experiments were performed to evaluate factors affecting sex reversal. The effect of not changing the water and increasing the temperature during hormone treatment was evaluated. The possible leaching out of hormone from hormone-treated feed was also investigated. Some of the sexually undifferentiated fry reared in water previously used for hormone treatment were sex-reversed indicating that hormone residues had accumulated during previous hormone treatment. Increasing the temperature during hormone treatment was observed to improve the efficiency of sex reversal, particularly feminisation. Results show that hormone leaches from hormone-treated feed suggesting that the observed accumulation of hormone residues could be partly due to leacheates.